Mamta Oil and Ghee Mills: Sales Target Dilemma - Sattar, Muhammad Muzamil; Sfodera, Fabiola (IIUM Journal of Case Studies in Management, 2023)
This case is about Mamta Oil and Ghee Ltd, operating under Fast Moving Consumer Goods industry of Pakistan. Currently company is standing in the last quarter of 2015 and is in the stage of evaluating its sales targets set for the year 2015. Mr. Asim Sheikh, the sales manager at MOG ltd and his team had achieved 92% of their sales targets in the first three quarters (July-March 2015) with the growth rate of 12.32 instead of 23 % which was expected. Mr. Asim is thinking to revisit the sales targets and revise them for the five regions of the company so that the expected growth rate along with 100% of targets is achieved. The case also bring discussion regarding launch of new product at the time when sales team is already striving to achieve their sales targets, which are not set appropriately.